Evaluating differences in setting expected body weight for children and adolescents in eating disorder treatment. Issue 3 (2nd December 2022) - Steinberg, Dori M.; Perry, Taylor R.; Freestone, David; Hellner, Megan; Baker, Jessica H.; Bohon, Cara
Abstract: Objective: Weight restoration or weight gain is a common goal in eating disorder treatment. However, approaches to determine expected body weight (EBW) vary. A standardized approach based on normative data for a patient's age and gender uses weight associated with median BMI (mBMI). An individualized approach predicts EBW based on a patient's individual growth trajectory. Little research has examined differences in these approaches. Method: Weight and clinical data were collected from patients ages 6–20 enrolled in virtual eating disorder treatment. EBW associated with mBMI was compared with EBW using the individualized approach. Linear mixed effects models examined differences in weight, eating disorder symptoms, depression, and anxiety, and whether EBW approach varied by patient characteristics. Results: Patients ( N = 609) were on average age 15.6 (2.29), 85% were cisgender female, and predominantly diagnosed with anorexia nervosa (83.1%). The individualized approach led to significantly higher EBW on average (mean difference = 8.4 lbs [SE: .75]; p < .001) compared to mBMI; 70% of patients had a higher EBW using the individualized approach. Notably, EBW varied based on gender and diagnosis and it took longer on average to achieve individualized EBW. Time was the strongest predictor of changes in psychosocial outcomes and there were no significant differences by EBW approach. Discussion: Results from this study indicate that an individualized approach led to significantly higher EBWs compared with using mBMI. As underestimation of EBW may lead to higher risk of relapse, eating disorder professionals should consider using an individualized approach for setting EBW. Public Significance: For eating disorder patients who need to gain weight, accurately estimating target body weight for eating disorder treatment is critical to recovery and preventing relapse. An individualized, patient‐centered approach to estimating target body weight more accurately estimated target body weight than the standardized, median body mass index approach. Using an individualized approach to treatment may improve a patient's likelihood of full recovery.